Efficiency Measurement of R&D Spending in Emerging Countries - Loukil, Kamilia (Review of Knowledge Economy, 2017)
This paper aims to measure efficiency of R&D spending in ten emerging countries. We estimate two stochastic frontier models where human and physical resources of R&D are the inputs employed to produce an output: patents in the first model and scientific publications in the second model. Empirical evidence shows that scores are higher for publication oriented efficiency than patent oriented efficiency. Moreover, our findings suggest that innovative countries, those with high R&D intensity, are not necessarily efficient in the use of their resources and vice versa.